Modified numerical solution for the dispersal of air pollutants from an elevated source - KUMAR, RAVINDRA; GUPTA, R. N. (MAUSAM, 1981)
While obtaining numerical solutions for the dispersal of pollutants from an elevated point source, truncation errors due to horizontal, advection invariably generate a fictitious viscosity, the magnitude of which soon exceeds vertical diffusion. This paper presents a numerical model in which the artificial viscosity appears to be very very small, i.e., negligible. The results are compared with those obtained by earlier methods and the improvement in results is observed. This shows that the presence of pseudoviscosity in a numerical method earlier used to give some error, especially at the advanced stages of time.